Micropatterned soft hydrogels to study the interplay of receptors and forces in T cell activation. (1st January 2021) - Zhang, Jingnan; Zhao, Renping; Li, Bin; Farrukh, Aleeza; Hoth, Markus; Qu, Bin; del Campo, Aránzazu
Abstract: The analysis of T cell responses to mechanical properties of antigen presenting cells (APC) is experimentally challenging at T cell-APC interfaces. Soft hydrogels with adjustable mechanical properties and biofunctionalization are useful reductionist models to address this problem. Here, we report a methodology to fabricate micropatterned soft hydrogels with defined stiffness to form spatially confined T cell/hydrogel contact interfaces at micrometer scale. Using automatized microcontact printing we prepared arrays of anti-CD3 microdots on poly(acrylamide) hydrogels with Young's Modulus in the range of 2 to 50 kPa. We optimized the printing process to obtain anti-CD3 microdots with constant area (50 µm 2, corresponding to 8 µm diameter) and comparable anti-CD3 density on hydrogels of different stiffness. The anti-CD3 arrays were recognized by T cells and restricted cell attachment to the printed areas. To test functionality of the hydrogel-T cell contact, we analyzed several key events downstream of T cell receptor (TCR) activation. Anti-CD3 arrays on hydrogels activated calcium influx, induced rearrangement of the actin cytoskeleton, and led to Zeta-chain-associated protein kinase 70 (ZAP70) phosphorylation. Interestingly, upon increase in the stiffness, ZAP70 phosphorylation was enhanced, whereas the rearrangements of F-actin (F-actin clearance) and phosphorylated ZAP70 (ZAP70/pY centralization) were unaffected. Our results show that micropatterned hydrogels allow tuning of stiffness and receptor presentation to analyze TCR mediated T cell activation as function of mechanical, biochemical, and geometrical parameters. Graphical abstract: Image, graphical abstract